Babymouse. [4], Rock star - Holm, Jennifer L.; Holm, Matthew (New York : Random House, 2006)
Babymouse daydreams of being a rock star, traveling around the world performing concerts, but in real life she will settle for playing the flute--and not being last chair--in the school band. Presented in graphic novel form.
Horn Book
Horn Book Starred
School Library Journal
Horn Book Starred, April 2007
Horn Book, September 2006
School Library Journal, September 2006
Keywords: Animals -- Juvenile fiction; Heroes -- Juvenile fiction; Mice -- Juvenile fiction; Musicians -- Juvenile fiction; Animals -- Fiction; Cartoons and comics; Heroes -- Fiction; Mice -- Fiction; Musicians -- Fiction; Animals -- Fiction; Comic books, strips, etc; Heroes and heroines -- Fiction; Mice -- Fiction; Musicians -- Fiction; Graphic novels